2006
DOI: 10.1007/s00168-005-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Are there really high-tech clusters? The geographic concentration of German manufacturing industries and its determinants

Abstract: The agglomeration of industries has recently received much interest both in empirical and theoretical work. Especially in Germany politicians became inspired by the notion of high-technology industry clusters, and regional policy has seen a wave of initiatives aiming at the formation of such clusters. This paper explores in a systematic way the geographic concentration of German manufacturing industries and relates it to industry characteristics and agglomeration forces proposed by theory. The main finding is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 29 publications
0
35
1
2
Order By: Relevance
“…10 Previous studies have observed that the scale of the territorial units may influence the degree to which industries are found to be concentrated (Ellison and Glaeser, 1997;Maurel and Sèdillot, 1999;Lafourcade and Mion, 2007;Alecke et al, 2006). Table 1 show that there is a strong tendency of the index to increase at the higher level of aggregation of the territorial units.…”
Section: The Concentration Of 2-digit Manufacturing and Service Indusmentioning
confidence: 65%
“…10 Previous studies have observed that the scale of the territorial units may influence the degree to which industries are found to be concentrated (Ellison and Glaeser, 1997;Maurel and Sèdillot, 1999;Lafourcade and Mion, 2007;Alecke et al, 2006). Table 1 show that there is a strong tendency of the index to increase at the higher level of aggregation of the territorial units.…”
Section: The Concentration Of 2-digit Manufacturing and Service Indusmentioning
confidence: 65%
“…26 Alecke et al (2006) apply the Ellison/Glaeser index to German high-tech manufacturing industries in order to examine "(…) the existence and strength of localization economies as opposed to urbanization economies which occur across industries" (Alecke et al 2006: 22). In this context, they use the notion of 'clusters' for agglomeration patterns of a three-digit industry.…”
Section: Cluster Identification Methodsmentioning
confidence: 99%
“…The meaning of 'geographic concentration' of clusters has led to various discussions and confusion [4][5][6]. Alcácer and Zhao [7] provide a new perspective in an ongoing debate.…”
Section: Clusters and Cluster Policymentioning
confidence: 99%
“…Getting credit (Cred) 3 Germany high, Austria low Ukraine high, Serbia low Enforcing contracts (EF) 4 Both high Both Low Political Transformation (PT) 5 Both transformed Ukraine low, Serbia medium Economic Transformation (ET) 6 Both transformed Ukraine low, Serbia medium Among the main findings, it can be stated that different patterns among activity bundles have been observed in cluster associations operating in various institutional environments (EU and non-EU countries/regions).…”
Section: Institutional Contextmentioning
confidence: 99%